Reliability and validity of the Malay version of the International Index of Erectile Function (IIEF-15) in the Malaysian population. - Quek, K.F.; Low, W.Y.; Razack, A.H.; Chua, C.B.; Loh, C.S. (Nature Publishing Group, 2002)
The objective of this study was to validate the Malay version of the International Index of Erectile Function (IIEF-15) in patients with lower urinary tract symptoms. Reliability and validity was assessed by using the test-retest while Cronbach's alpha was used to assess internal consistency. Effect size 5was evaluated to assess the sensitivity to change in the pre-transurethral resection of the prostate (TURP) vs post-TURP. Internal consistency was excellent. A high degree of internal consistency was observed for each of the 15 items and five domains (Cronbach's alpha value=0.56 and higher and 0.74 and higher, respectively). Test-retest correlation coefficient for the 15 items and domains scores showed no significant changes. Intraclass correlation coefficient for 15 items and domains were high (ICC=0.59 and above). It can be concluded that the Mal-IIEF-15 is suitable, reliable, valid and sensitive to clinical change in the Malaysian population.